2018
DOI: 10.1002/jbm.a.36540
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visible and UVA phototoxicity in neural culture systems micropatterned with digital projection photolithography

Abstract: Photopolymerization provides a favorable method for hydrogel formation due to its simplicity, convenience, and versatility. However, the light exposure required to initiate photopolymerization is known to have a cytotoxic effect on encapsulated cells. Here, a 3D in vitro model of the nervous system microenvironment, micropatterned through the use of digital projection photolithography using a single hydrogel formulation that cross-links similarly under ultraviolet A (UVA, 315-400 nm) and visible light (400-700… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 73 publications
(119 reference statements)
1
19
0
Order By: Relevance
“…S1D), indicating that any physiological differences among conditions are not a result of declining cell health. Consistent with previous reports ( 41 46 ), immunofluorescent staining of total nerve growth with the neuron-specific cytoskeletal protein, β-III-tubulin, confirmed that stiff, gelatin methacrylate–based ECM promoted DRG neurite outgrowth and inhibited SCDH neurite outgrowth in monoculture (fig. S1E).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…S1D), indicating that any physiological differences among conditions are not a result of declining cell health. Consistent with previous reports ( 41 46 ), immunofluorescent staining of total nerve growth with the neuron-specific cytoskeletal protein, β-III-tubulin, confirmed that stiff, gelatin methacrylate–based ECM promoted DRG neurite outgrowth and inhibited SCDH neurite outgrowth in monoculture (fig. S1E).…”
Section: Resultssupporting
confidence: 92%
“…We first sought to identify an optimal ECM composition that promotes the emergence of the appropriate structure-function relationship between DRG and SCDH nerve tissue. Our laboratory has previously had success growing three-dimensional nerve cultures in both gelatin methacrylate and Matrigel-based hydrogels and hypothesized on the basis of previous reports ( 41 46 ) that modulation of gel stiffness could be used to direct neurite growth. Therefore, we designed gelatin methacrylate and Matrigel-based gel formulations that would result in ECM of various stiffness and compared morphology and physiology of cultures across gel formulations to identify the optimal ECM.…”
Section: Methodsmentioning
confidence: 99%
“…To facilitate the preparation of cross-sections of myelinated axons, these cells were co-cultured within a microchannel mold that promotes the alignment of axons along the channel in one direction. The microchannel mold was constructed by adding a 10% (w/v) PEG-diacrylate (Mn 1000; Polysciences Inc., Warrington, PA) and 0.5% (w/v) Irgacure 2959 in PBS solution to a collagen-coated transwell 43 , 84 , 85 . A negative mask was used to create the microchannel, followed by irradiation of the light-sensitive media with 181 mW/cm2 UV light for 30 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…This resulted in glycidyl methacrylate-dextran (MeDex), the composition of which was confirmed using 1 H NMR [(D 2 O) 𝛿 6.1–5.7 (m, 2H, CH 2 ), 𝛿 5.2 (m, 1H, CH), δ 4.9 (m, 1H, CH), δ 1.9 (s, 3H, CH 3 )] with substitution degree of 42% 32,34,35 . Finally, a gel composition of MeDex 50% (w/v), arginine (0.1% (w/w) of MeDex), riboflavin (0.001% (w/w) of MeDex), TEMED (0.2% (v/v) of the final solution) was prepared for photocrosslinking 27 .…”
Section: Methodsmentioning
confidence: 99%
“…However, this objective was challenged by a number of conflicting design constraints, including hydrogel stability, cell viability, transparency, and ease of histology. Self-assembling hydrogels were susceptible to detaching from PEG hydrogel molds 26 while photocrosslinking was found to be disproportionately harmful to Schwann cells 27 . Preliminary work with alternative hydrogels showed that methacrylated dextran cured with visible light and a riboflavin-arginine photoinitiator was less phototoxic to Schwann cells, but its yellowish translucent color made it difficult to visualize the tissue for placement of extracellular field electrodes.…”
Section: Introductionmentioning
confidence: 99%